Survey of the anti–factor IX immunoglobulin profiles in patients with hemophilia B using a fluorescence‐based immunoassay. (17th September 2016) - Boylan, B.; Rice, A. S.; Neff, A. T.; Manco‐Johnson, M. J.; Kempton, C. L.; Miller, C. H.; ,
Abstract : Essentials Studies characterizing neutralizing antibodies (inhibitors) in hemophilia B (HB) are lacking. The current study describes anti–factor (F) IX antibody profiles in 37 patients who have HB. Anti‐FIX IgG4 levels exhibited a strong positive correlation with Nijmegen–Bethesda results. These data will help to more clearly define, predict, and treat alloantibody formation in HB. Summary: Background: Hemophilia B (HB) is an inherited bleeding disorder caused by the absence or dysfunction of coagulation factor IX (FIX). A subset of patients who have HB develop neutralizing alloantibodies (inhibitors) against FIX after infusion therapy. HB prevalence and the proportion of patients who develop inhibitors are much lower than those for hemophilia A (HA), which makes studies of inhibitors in patients with HB challenging due to the limited availability of samples. As a result, there is a knowledge gap regarding HB inhibitors. Objective: Evaluate the largest group of patients with inhibitor‐positive HB studied to date to assess the relationship between anti‐FIX antibody profiles and inhibitor formation. Methods: A fluorescence immunoassay was used to detect anti‐FIX antibodies in plasma samples from 37 patients with HB. Results: Assessments of antibody profiles showed that anti‐FIX IgG1‐4, IgA, and IgE were detected significantly more often in patients with a positive Nijmegen–Bethesda assay (NBA). All NBA‐positive samples were positive for IgG4 . Anti‐FIX IgG4 demonstrated a strong correlation with the NBA, while correlations were significant, yet more moderate, for anti‐FIX IgG1‐2 and IgA. Conclusions: The anti‐FIX antibody profile in HB patients who develop inhibitors is diverse and correlates well with the NBA across immunoglobulin (sub)class, and anti‐FIX IgG4 is particularly relevant to functional inhibition. The anti‐FIX fluorescence immunoassay may serve as a useful tool to confirm the presence of antibodies in patients who have low positive NBA results and to more clearly define, predict, and treat alloantibody formation against FIX.